2020
DOI: 10.1186/s13054-020-2762-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of venous blood analysis at the start of CPR in non-traumatic out-of-hospital cardiac arrest: association with ROSC and the neurological outcome

Abstract: Background: The knowledge of new prognostic factors in out-of-hospital cardiac arrest (OHCA) that can be evaluated since the beginning of cardiopulmonary resuscitation (CPR) manoeuvres could be helpful in the decisionmaking process of prehospital care. We aim to identify metabolic variables at the start of advanced CPR at the scene that may be associated with two main outcomes of CPR (recovery of spontaneous circulation (ROSC) and neurological outcome). Methods: Prospective observational study of all non-traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 27 publications
2
35
1
4
Order By: Relevance
“…Corral Torres et al [1] observed a significant relationship between severe alterations of venous blood gas variables and potassium at the start of cardiopulmonary resuscitation (CPR) of non-traumatic out-of-hospital cardiac arrest (OHCA) and low return of spontaneous circulation (ROSC) rate and neurological prognosis. The authors should be congratulated for their noteworthy study on this relevant question; nevertheless, we believe that the results interpretation requires words of caution because of some issues.…”
Section: Romain Jouffroy and Benoît Vivien *mentioning
confidence: 99%
See 1 more Smart Citation
“…Corral Torres et al [1] observed a significant relationship between severe alterations of venous blood gas variables and potassium at the start of cardiopulmonary resuscitation (CPR) of non-traumatic out-of-hospital cardiac arrest (OHCA) and low return of spontaneous circulation (ROSC) rate and neurological prognosis. The authors should be congratulated for their noteworthy study on this relevant question; nevertheless, we believe that the results interpretation requires words of caution because of some issues.…”
Section: Romain Jouffroy and Benoît Vivien *mentioning
confidence: 99%
“…We thank Drs. Jouffroy and Vivien from SAMU, with whom we shared so much, for their letter to our recent article regarding the prognostic value of blood analysis at the start of CPR in non-traumatic out-of-hospital cardiac arrest [1]. Firstly, whatever the difficulties in obtaining the first venous line, the truth is that it is the first sample available in every real situation.…”
Section: Romain Jouffroy and Benoît Vivien *mentioning
confidence: 99%
“…[9] World J Emerg Med, Vol 14, No 2, 2023 Factors that predict ROSC and long-term survival in patients with OHCA have been studied, including prehospital information, such as age, sex, witnesses, bystander cardiopulmonary resuscitation (CPR), cause leading to cardiac arrest, and initial rhythm. [10] According to blood tests, various factors, such as levels of K + , [11,12] Na + , [13] blood glucose, [13] ammonia, [14] brain natriuretic peptide, [15] lactate, [16][17][18] and free thyroxine 4, [19] have been reported to affect the prognosis of OHCA. Moreover, significant activation of coagulation occurs as a part of the pathogenesis after cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pre-arrest factors such as witnessed cardiac arrest, bystander CPR, and the presence of shockable rhythms, parameters obtained during CPR might add more accuracy to the prognostication. Some studies have reported that pH and base excess (BE) are associated with ROSC in OHCA 6 8 . Recently, two studies have shown that higher levels of paO 2 are significantly associated with increased rates of survival to hospital admission in OHCA 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%